2018
DOI: 10.5089/9781484377451.001
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Effects of Tax Rate and Base Changes: Evidence from Fiscal Consolidations

Abstract: This paper examines the macroeconomic effects of tax changes during fiscal consolidations. We build a new narrative dataset of tax changes during fiscal consolidation years, containing detailed information on the expected revenue impact, motivation, and announcement and implementation dates of nearly 2,500 tax measures across 10 OECD countries. We analyze the macroeconomic impact of tax changes, distinguishing between tax rate and tax base changes, and further separating between changes in personal income, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Much work has followed and found that the contractionnary effect of fiscal consolidation is indeed important (Jordà and Taylor, 2016), especially in periods of low growth (Blanchard and Leigh, 2013;De-Long and Summers, 2012;Fatás and Summers, 2018). However, the empirical approach to study the fiscal multiplier has experienced a major shift with Romer and Romer (2010), who first introduced a narrative dataset of fiscal events, and this methodology has been widely adopted by the literature (as in Dabla-Norris and Lima, 2018;Amaglobeli et al, 2019). In this new approach, the exogeneity of the fiscal shock with respect to the business cycle is ensured by the selection of fiscal events based on their explicit motivation according to different official sources (government and international organizations reports, parliamentary documents or public discourses for example).…”
Section: Related Literaturementioning
confidence: 99%
“…Much work has followed and found that the contractionnary effect of fiscal consolidation is indeed important (Jordà and Taylor, 2016), especially in periods of low growth (Blanchard and Leigh, 2013;De-Long and Summers, 2012;Fatás and Summers, 2018). However, the empirical approach to study the fiscal multiplier has experienced a major shift with Romer and Romer (2010), who first introduced a narrative dataset of fiscal events, and this methodology has been widely adopted by the literature (as in Dabla-Norris and Lima, 2018;Amaglobeli et al, 2019). In this new approach, the exogeneity of the fiscal shock with respect to the business cycle is ensured by the selection of fiscal events based on their explicit motivation according to different official sources (government and international organizations reports, parliamentary documents or public discourses for example).…”
Section: Related Literaturementioning
confidence: 99%
“…5 The underlying assumption is that the feedback effect of output on tax revenues is controlled by a constant, country-specific output-gap elasticity. To obtain the cumulative multipliers of a permanent tax change, I use the local projection method proposed by Jordà (2005) and Jordà, Schularick, and Taylor (2015) and employed by Dabla-Norris and Lima (2018) to estimate dynamic multipliers for a country panel.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy exceptions are Riera-Crichton, Vegh, and Vuletin (2016) and Gunter et al (2018) who estimate value-added tax multipliers. Dabla-Norris and Lima (2018) estimate personal income tax, corporate tax, and value-added tax multipliers and differentiate between tax rate and tax base changes. Yet, multipliers are assumed to be constant along the business cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Dabla-Norris and Lima (2018) also investigate the macroeconomic effects (including output effect), separating effects of tax rate and base changes. Their result on the output effect of VAT rate indicates that an increase in a VAT rate has a negative and statistically significant impact on output in the short run.9 In contrast, Institute for Fiscal Studies (2011) do not specify which fiscal element is adjusted when each VAT component changes.10 De Mello (2009) point out other structural factors associated with C-efficiency, such as the efficiency of tax administration and the country's governance indicators.…”
mentioning
confidence: 99%